2017
DOI: 10.1186/s12893-017-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the regional, hospital and individual levels of antibiotic use in gallstone surgery in Sweden

Abstract: BackgroundAntimicrobial resistance may be promoted by divergent routines and lack of conformity in antibiotic treatment, especially regarding the practice of antibiotic prophylaxis. The aim of the present study was to assess differences in gallstone surgery regarding antibiotic use in Sweden.MethodsThe study was based on data from the Swedish Register for Gallstone Surgery and ERCP (GallRiks) 2005–2015. Funnel plots were used to test impact of grouping factors, including, hospital and surgeon and to identify u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This study was conducted to assess differences in gallstone surgery regarding antibiotic use in Sweden. Significant disparities were found only between hospitals and surgeons [20]. Health service utilization is influenced not only because of the distribution of health service facilities in the region but also influenced by human distribution and supporting environment, which influence decision-making and behavior in relation to service utilization [21].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to assess differences in gallstone surgery regarding antibiotic use in Sweden. Significant disparities were found only between hospitals and surgeons [20]. Health service utilization is influenced not only because of the distribution of health service facilities in the region but also influenced by human distribution and supporting environment, which influence decision-making and behavior in relation to service utilization [21].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to assess differences in gallstone surgery regarding antibiotic use in Sweden. Signi cant disparities were found only between hospitals and surgeons (17). Health service utilization is in uenced not only because of the distribution of health service facilities in the region, but also in uenced by human distribution and supporting environment, which in uence decision making and behavior in relation to service utilization (18).…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis with antibiotics can reduce the risk of bacterial dissemination and, consequently, of post-surgical infections. In similar studies, it was suggested that the use of prophylactic antibiotics in elderly people with comorbidities would be indicated to reduce the risk of infection [32,33].…”
Section: Discussionmentioning
confidence: 99%